Prosedur Pembukaan Rekening Tabungan Pada PT Bank BPD DIY Cabang Bantul - Salma Azalea Zahra; Diana Airawaty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Bank BPD DIY is one of the self-help tools in the banking industry, as a source of regional income, regional development revitalization, regional development acceleration, regional money management/regional money storage. Opening an account is a form of bank business to collect money from the community to ensure convenience . Therefore, it is very important to have guidelines in making savings. Aside from being a form of risk management, this deposit fulfillment manual aims to increase each employee's insight into bank financing products. This implementation can be done through the account opening process. So that opening an account requires procedures that must be followed by prospective customers